Comparison between Transesterification Reaction with Microwave Heating and Conventional Heating for Biodiesel Production from Coconut Oil with Alkaline Catalyst - Boangmanalu, Srunika; Ginting, Elfrida (Universitas Negeri Medan, 2023)
Biodiesel is a biofuel made from vegetable oil through an esterification-transesterification process. The process of making biodiesel is carried out by conventional heating methods and microwave heating. The reaction process was carried out according to the specified variables, with a concentration of 0.1% of the volume of methanol and a variable microwave power of 135, 225 and 315 watts with time variations of 5, 3 and 1 minute, as well as conventional heating at 60°C for 1 hour. The best result is the one using microwave heating with a power of 315 watts for 1 minute. The best biodiesel yield is 88.879%, with water content of 0.01%, an acid number of 0.56 Kg-KOH/g, a density of 0.892 g/mL and a viscosity of 2.617 cSt. The best result of biodiesel oil in comparison of is using the microwave heating method.